Reflective Insights and Future Directions in Mindfulness Education in Taiwan: A Comparative Study of the Buddhist "Four Foundations of Mindfulness" and Kabat-Zinn's Practices - Fa-Zhao Shi; An Kang (National Taipei University of Education, 2024)
Since its inception by Dr. Kabat-Zinn, Mindfulness-Based Stress Reduction (MBSR) has led to various mindfulness interventions and gained positive feedback in many fields. This paper extracts the shared mindfulness mechanisms emphasized by Kabat-Zinn's MBSR and the Buddhist "Four Foundations of Mindfulness," assesses their applicability to mindfulness education, and compares their differences in objectives and skills, serving as a reference for the future development of mindfulness education in Taiwan. The study finds that mindfulness education in Taiwan mainly follows Kabat-Zinn's guidance, focusing on basic practices of "body, feelings, and mind," with less involvement in higher-level psychological insights. In the aspect of "dharmas," Kabat-Zinn incorporated Zen concepts, a practice that has seen limited attention and utilization in Taiwan, which also rarely addresses goal-oriented elements. This paper suggests that mindfulness education in Taiwan should emphasize the guidance of "impermanence and non-self" and the systematic thinking of "dharmas," striving to present these concepts in accessible language to mitigate concerns over religiosity. To enhance mindfulness education in Taiwan, two key areas should be addressed: first, the scope of mindfulness research and practice should expand to include "higher-level psychological qualities"; second, government authorities should consolidate resources to establish a mindfulness research and teacher training center, aiming to develop a comprehensive and practical pedagogical framework. Only with solid academic research and institutional support can mindfulness education in Taiwan be truly strengthened, thereby enhancing public well-being and promoting holistic development.